Knowledge and awareness on usage of mouth masks among dental fraternity during this pandemic COVID-19: A cross-sectional study - Ravi, Ravichandra; Athkuri, Srividya; Ponugubati, Charishma Chowdary; Borugadda, Roopesh; Pamidimukkala, Sahithi; Afraaz, Abdul (Asian Journal of Medical Sciences, 2020)
Background: The pandemic caused by novel coronavirus (SARS-CoV-2) in Wuhan, China, in December 2019 is a highly infectious disease. The World Health Organization (WHO) has declared the outbreak of Corona Virus Diseases (COVID 19) as a global public health emergency. Currently, research on novel coronaviruses is still in the primary stage. Aims and Objective: The aim of this study is to assess knowledge and awareness on the usage of mouth masks among dental fraternity during this pandemic COVID-19. Materials and Methods: A total of 507 dentists from the Andhra Pradesh (India) region completed a questionnaire-based survey on knowledge, awareness, and infection control measures, such as usage of mouth masks during the pandemic COVID -19. The questionnaire was tailored from the guidance and the information provided for healthcare workers issued by the US Centres for Disease Control and Prevention (CDC). A suitable sampling method was used for the collection of data, and the distribution of responses was presented as percentages. Explanatory statistics were performed for all groups based on the percentage of correct responses. Results: A total of 530 participated in the survey, out of which 507 dentists completely answered the survey, and the response rate was 95.6%. Among the respondents, general practitioners and postgraduates accounted for 58.8% and 41.2%, respectively. There was a statistically significant difference for all the questions solicited among the respondents. General or private practitioners seem to be more aware than postgraduates, as they have answered correctly (>65%) for almost all the questions. Conclusion: The inputs from the study help us to throw some light and fill up space where required. There is a specific and strong need to implement periodic educational programmes and training sessions on infection control practices for COVID-19 among dentists in particular.